Expansion of the (CTG)(n) repeat in the 5′-UTR of a reporter gene impedes translation - Raca, Gordana (Oxford University Press, 2000)
Effects of d(CAG)(n)·d(CTG)(n) repeats on expression of a reporter gene in human cell culture were studied using transient transfection, RNase protection and coupled transcription/translation assays. Cloning these repeats into the reporter 3′-UTR did not affect gene functioning. In contrast, placing the repeats in the reporter 5′-UTR led to strong inhibition of expression. This inhibition depended on the repeat orientation, being prominent only when the (CTG)(n) tracts were in the sense strand for transcription. Further, the strength of inhibition increased exponentially with an increase in repeat length. Our data indicate that expanded (CTG)(n) repeats prevent efficient translation of the reporter mRNA both in vitro and in vivo. We suggest that formation of stable hairpins by (CUG)(n) runs of increasing length in the 5′-UTR of a mRNA progressively inhibits the scanning step of translation initiation. This points to a novel mechanism of regulating gene expression by expandable d(CTG)(n) repeats.